ANALISIS LINGKUNGAN EKSTERNAL DAN INTERNAL SEBAGAI FORMULASI STRATEGI BISNIS. ( Kasus Penerapan Analisis SWOT Pada Perusahaan Otobus Sampri Trayek Dolok Sanggul – Medan, Kecamatan Dolok Sanggul, Kabupaten Humbang Hasundutan, Provinsi Sumatera Utara ) - Sihombing, Marganda Parsaulian; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted at PO Sampri Dolok Sanggul station with Doloksanggul-Medan route. This business engaged in the transportation lease public transport carrying passengers with Dolok Sanggul-Medan route. This study aims to determine the SWOT analysis as strategy formulation and preparation steps forward are intended to define the strategic objectives and corporate finance, as well as designing strategies to achieve these objectives in order to provide the customer the best value.This research is a descriptive qualitative approach, where there is no population and sample. This research using key informants to obtain the required information. The data used are primary data and secondary data.From the results of the analysis can know that there are some alternative strategies that can be used as a tool to win the competition on the route Dolok Sanggul-Medan, and the results of this analysis to formulate long-term strategies.Keyword : SWOT (Strengths, Weakness, Opportunity, Threat) SWOT analysis, alternative strategy P.O Sampri Dolok Sanggul-Medan